Expat-friendly public policy for ıstanbul: From discourse to action - BOZLAĞAN, Recep; YILMAZ, Nail; DAOUDOV, Murat; CALLET-RAVAT, Lauranne (My University, 2015)
In the developed countries there is a growing discourse about attracting human capital as one of the key tools to strengthen the economic competitiveness. This phenomenon is also visible at local level, notably through increasing focus on city branding and emphasis on attraction of talents and investors, and increased involvement of local/regional governments in this field. Turkey also steadily adopts similar discourse in its policy documents such as the national and local plans and strategy papers; these documents emphasize the goal of becoming “center of attraction” and gaining qualified labor force. Istanbul plays an important role as a major experimentation site for the success of such policy. In this framework Turkey transforms and modernizes its migration policy, and the officials call for various policies and practices that would create favorable living and working conditions for foreigners or expats. However this approach is not yet translated into concrete actions that would have tangible impact on public sector policies and institutions in Istanbul, whether central or local/metropolitan government units, and that would be visible to the expats themselves. The analysis of the findings of the survey realized by the authors in order to measure the perception of public services in Istanbul by the expats, combined with other resources, suggests that, despite the higher level discourse, public institutions lack concrete policies on the ground. The article therefore formulates several recommendations to raise the awareness of decision-makers and to develop expat-friendly public policy in Istanbul.
Keywords: Expat, Qualified Labor Migration, Attraction of Human Capital, Migration Policy, Harmonization, Integration Policy, Expat-Friendly Public Policy.